2022
DOI: 10.1332/251569121x16268740317724
|View full text |Cite
|
Sign up to set email alerts
|

Political regimes and deaths in the early stages of the COVID-19 pandemic

Abstract: This article provides a quantitative examination of the link between political institutions and deaths during the first 100 days of the COVID-19 pandemic. We demonstrate that countries with more democratic political institutions experienced deaths on a larger per capita scale than less democratic countries. The result is robust to the inclusion of many relevant controls, a battery of estimation techniques and estimation with instrumental variables for the institutional measures. Additionally, we examine the ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 51 publications
2
42
0
Order By: Relevance
“…In accordance with Cepaluni et al (2020), the former effect is even more pronounced in terms of the reported death toll and cases per capita (see Models 2–4 and 6–8). The impact of regulation and transparency on the reported death toll is significant and highly positive for both Europe and Africa, although these coefficients decrease with the extension of the time window.…”
Section: Resultssupporting
confidence: 72%
“…In accordance with Cepaluni et al (2020), the former effect is even more pronounced in terms of the reported death toll and cases per capita (see Models 2–4 and 6–8). The impact of regulation and transparency on the reported death toll is significant and highly positive for both Europe and Africa, although these coefficients decrease with the extension of the time window.…”
Section: Resultssupporting
confidence: 72%
“…Thus, we highly recommend that future research can better answer this question. Second, it is suggested that stringency may have some negative effects on a society along with its positive effect on the control of the COVID-19 pandemic [14,18]. However, this study primarily focused on the bright side of stringent government containment and closure policies, and provided little evidence on the dark side of it.…”
Section: Discussionmentioning
confidence: 93%
“…Diao et al [8] also noted that as the Chinese government implemented a strict lockdown policy at the beginning of the COVID-19 pandemic, there was no association between population density and the COVID-19 spread in China. According to the Oxford COVID-19 Government Response Stringency Index, which are widely used in extant studies [1,14] (refer to the Codebook for the Oxford Covid-19 Government Response Tracker for detailed information, https://github.com/OxCGRT/covid-policy-tracker/blob/master/documentation/ codebook.md#codebook-changelog, access on 25 September 2020), governmental policies can be classified into four types: (1) containment and closure policies; (2) economic policies;…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations